Native T1 in Discrimination of Acute and Convalescent Stages in Patients With Clinical Diagnosis of Myocarditis - Rocío Hinojar; Lucy Foote; Eduardo Arroyo; Tom Jackson; Andrew Jabbour; Chung-Yao Yu; Jane McCrohon; David Higgins; Gerry Carr‐White; Manuel Mayr; Eike Nagel; Valentina O. Püntmann (2014)
This study investigated whether T1 mapping by cardiac magnetic resonance (CMR) reflects the clinical evolution of disease in myocarditis and supports its diagnosis independently of the disease stages. Acute viral myocarditis is characterized by a range of intracellular changes due to viral replication and extracellular spill of debris within days of viral infection. Convalescence may be characterized by a chronic low-grade inflammation leading to ventricular remodelling, but also a complete resolution of myocardial changes. Patients with clinical diagnosis of viral myocarditis (N = 165) underwent routine clinical CMR protocol (1.5- and 3.0-T) for assessment of cardiac function and structure, and tissue characterization with T2-weighted imaging and late gadolinium enhancement. T1 mapping was obtained in a mid-ventricular short-axis slice before and >20 min after administration of 0.2 mmol/kg of gadobutrol. Compared with control subjects (n = 40), T1 indexes were increased in patients with myocarditis. Patients with acute symptoms (n = 61) had higher values of T1 indexes compared with patients in clinical convalescence (n = 67). Native T1 is an independent discriminator between health and disease, as well as a discriminator between acute and convalescent stage of the disease. Native T1- was superior to T2-weighted imaging and late gadolinium enhancement with high diagnostic accuracy and positive and negative predictive values. Using pre-defined cutoff values for normal ranges, we demonstrated that acute myocarditis can be independently identified by native T1 of >5 SD above the mean of normal range, whereas convalescence is best defined by either abnormal native T1 (>2 SD) or presence of late gadolinium enhancement. We prospectively tested a new diagnostic algorithm in an independent dataset of patients with clinical diagnosis of myocarditis and achieved similar diagnostic performance. The new diagnostic algorithm using native T1 can reliably discriminate between health and disease and determine the clinical disease stage in patients with a clinical diagnosis of myocarditis.